ELECTRONIC TEXTBOOKS IN THE EDUCATIONAL PROCESS-NEW REALITY - Pulatov Jobirxon Djamalovich (Academia Science Repository, 2023)
Recently the processes of creating digital textbooks in the hyper-text format and their introduction into studying have intensified. Both Russian and foreign educational institutions are engaged in developing guidelines and requirements to digital textbooks, e-learning courses and software. Despite a considerable number of papers, the technology of using a digital textbook in classroom has not been studied sufficiently yet. Since a comprehensive digital textbook is more than an electronic version of a printed book, but rather a set of technical means, i.e. a product that comprises text, sound, video, graphic design and animation, the transition to learning with digital textbooks has its own advantages. Foreign languages stand out from other courses as they require simulating artificial language environment in class. Using classroom technology thus becomes an asset as it allows to make the learning environment more authentic due to the introduction of talks by native speakers. The authors of the article share their experience of applying digital textbooks designed on the basis of the SunRav Book Office software in foreign language classes at the Military (Combined Arms) Institute. The article considers key features of the digital textbook that allow raising the quality of teaching and learning a foreign language, including the visual, multimedia, information search and self-control aspects.